Penerapan Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di MTs Darul Aitam Jerowaru: Implementation of School-Based Management in Improving the Quality of Education at MTs Darul Aitam Jerowaru - Lalu Moh Fahri; Ayatullah; Hadiami Hilmi; Diah Ayu Puspita Sari; Hilmiati (Al-Gafari : Manajemen dan Pendidikan, 2026)
This study aims to analyze and describe the implementation of School-Based Management carried out by madrasahs in improving the quality of education at MTs Darul Aitam Jerowau. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that MTs Darul Aitam Jerowaru has implemented School-Based Management systematically. School-Based Management is carried out in the form of granting authority to school organizations to carry out their duties and functions properly. So that it can improve the quality of education. The implementation of School-Based Management has contributed positively to improving the quality of education. Although there are several obstacles such as facilities and infrastructure, the madrasah continues to strive to overcome these obstacles through good management. Thus, school-based management carried out in madrasahs has proven effective in supporting the quality of education at MTs Darul Aitam Jerowau.